PERSPEKTIF HUKUM LINGKUNGAN INTERNASIONAL LEMBAGA CTI - Salma Laitupa; Eka Dewi Kartika (The Juris, 2020)
Coral Triangle Initiative or CTI agreement in the form of a CTI Regional Plan of Action by 6 countries, namely Indonesia, Malaysia, Papua New Guinea, the Republic of the Philippines, Solomon Islands, and the Democratic Republic of Timor Leste in the form of the CTI Regional Plan of Action to increase protection of marine resources and beaches that are in the coral triangle area in the sea area of the CT6 country. The CTI Regional Plan of Action is an important matter in saving the diversity of the world's marine biodiversity, especially fish and coral reefs. The Coral Triangle (CT6) countries, namely Indonesia, Malaysia, Papua New Guinea, the Republic of the Philippines, Solomon Islands, and the Democratic Republic of Timor Leste, have agreed that the Regional Plan of Actions (RPOA) is a reference for implementing the Initiative in their respective countries. In particular, CT6 countries entered into agreements to achieve 5 (five) main objectives.